Molecular Study to Determine The Prevalence of Sugar-Degrading Bacteria in The Intestines of Poultry and Environmental Analysis Methods - Stiwey, Lubna Abedulraheem; Mohammed, Doaa; Stiwey, Nida Abedulraheem (American Journal of Biomedicine and Pharmacy, 2025)
The have a look at sought to apprehend the intestinal microbiome of broiler birds and the hen manufacturing surroundings as a whole with reference to the presence and relevance of the sugar-degrading bacteria including Lactobacillus and Bifidobacterium species. Environmental samples have been taken from litter, water, and feed, and blended with a gut microbiome analysis of excessive-appearing and coffee-appearing broiler flocks the use of 16S rRNA P C R and sequencing and other molecular strategies. The effects indicated that 35% ± five% of the the total intestinal bacterial biota composed the Lactobacillus SSU species and 15% ± 3% of the Bifidobacterium SSU species. These sugar degrading micro organism were additionally present inside the rearing environment, but at decrease and relative frequencies. In precise, the variety and amount of Lactobacillus and Bifidobacterium species have been an awful lot better in broiler flocks which have high production overall performance than in those of low manufacturing performance. The relative abundance of these useful microorganisms become also related to stepped forward feed conversion ratio and increase charge of the chickens. These findings spotlight the significance of sugar-degrading bacteria on the gut fitness and productivity of different bird production structures. The findings indicate that there may be potential for improving the sustainability and efficiency of broiler fowl operations through focused strategies like selective breeding or nutritional remedies that goal to optimize the makeup of the gut microbiome. The take a look at sheds light on the importance of sure species of bacteria, including Lactobacillus and Bifidobacterium, to the digestive systems of chickens and offers promising avenues for optimization efforts on this sector.